In situ evaluation of the references properties of structural timber members. Use of available tools and information - Saporiti Machado, J. (2013)
Survey of existing timber structures often includes the need to allocate mechanical properties to structural timber members. This task has to take into account the huge variability of timber's properties (within and between species), characteristic that differentiates this material from other structural materials (e.g. concrete and steel). For many decades, and still now, the application of visual strenght standards is the main or only procedure used for this task. despite the large number of other non and semi-destructive technique developed their regular application to in situ assesment of timber's mechanical properties is still almost non-existent. The present paper discusses possible ways to use and combine information from visual grading standards and non and semi-destructive techniques to predict the reference properties of timber members in service. The discussion has in mind studies conducted over the last years and the information provided by different guidelines, standards or papers recently published.